A Theoretical Approach to the Study of Wasta - Tucker, Lewis (2014)
The phenomenon of Wasta (aka Vitamin W) in the Arab culture is almost as old as the culture itself. Wasta is commonly described in terms of the ability of individuals to influence others through powerful social contacts. The purpose of this research is to develop a conceptual model of Wasta grounded in French and Raven's (1959) power constructs that govern the nature of social relationships, expectancy theory and information processing. Specifically, the expert, legitimate, referent, coercion and reward dimensions of power and the expectancy construct of motivational force are integrated through an information processing framework and used to guide a theoretical examination of the Wasta phenomenon. The model is utilised to develop application scenarios resulting in the formulation of research propositions and the associated methodology to assess the model's efficacy. Implications for researchers, organisational strategists and public policy makers are presented. Finally, limitations and future research directions are examined.